Understanding Unemployment Normalization: Individual Differences in an Alternative Experience With Unemployment - Houssemand, Claude; Thill, Steve; Pignault, Anne (Frontiers in Psychology, 2020)
Unemployment is a major concern of societies and people around the world. In addressing this phenomenon, the literature has suggested a change in unemployed people’s perceptions of this transition period. In this paper, we apply a differential approach to explore the concept of unemployment normalization, an individual emotional regulation process. The results show how the global socioeconomic context and some individual and psychological variables influence the normalization of unemployment. Thus, the age of the person but also work involvement, coping strategies, locus of control, and level of self-esteem have indirect differential effects, mediated by unemployment normalization dimensions, on unemployed people’s perceived health. Only neuroticism has a direct link to subjective well-being. These results offer a new understanding of the perception of unemployment and are also discussed in the area of career and vocational counseling.